Effect of parent selection and crosses of Pyrus ussuriensis on the early-bearing ability of F1 progenies. Issue 1 (July 2020) - Wang, Qiang; Zhang, Maojun; Lu, Mingyan; Wu, Chunhao; Yan, Xingkai; Li, Honglian; Ding, Lihua
Abstract: In order to investigate the effect of combinations of different pear varieties and their descendants and other cultivated pear varieties on the early fruiting of F1 generation, the individual plant Numbers of F1 generation of 17 hybrid combinations were investigated. The results showed that: 17 combinations of 1175 hybrid seedlings, 15 combinations of fruit age in 6∼8 years, 8 years of birth there are two combinations of Hanxiangli×Jinxiangshui, Dacili× Eli1 did not blossom. Among the flowering combinations, there were differences among different maternal combinations. The flowering plant rate of the combination with Dacili as the parent was the highest, which was 12.14%.Hanxiangli was the second 9.42%.Jinxiangshui was the lowest 6.43%.There were significant differences in the number of flowering plants in the offspring population in different combinations of maternal parent and paternal parent, indicating that parental parent had a significant influence on the age of bearing fruit in the hybrid population. There was a big difference in the age of the first fruit in F1 generation in the combination of pear varieties in other cultivation systems. However, the progeny of the parent and parent groups of Pyrus ussuriensis had a lower flowering individual plant, and the combination of Pyrus ussuriensis × Pyrus ussuriensis was zero. It can be seen that the seed sex of Pyrus ussuriensis has a great influence on the early and late fruit age of offspring.